Lake-level stratigraphy and geochronology revisited at Lago (Lake) Cardiel, Argentina, and changes in the Southern Hemispheric Westerlies over the last 25 ka. (1st December 2017) - Quade, J.; Kaplan, M.R.
Abstract: Paleoshorelines around Lago (Lake) Cardiel in southern Argentina (S48.9°, W71.3°; ∼275 m) record substantial changes in lake area over the past 25 ka. Our results combined with previous research show that during the last glacial maximum (or LGM, 23–21 ka), the lake stood at near modern levels, but had nearly dried up by ∼13 ka. Between 11.3 and 10.1 ka the lake reached its highest point (+54–58 m) and greatest extent in at least the last 40 ka. Lake levels dropped thereafter and experienced two lower-lake periods: 8.5–7.5 ka and 5–3.3 ka; and two higher-lake periods: 7.4–6 and ∼5.2 ka. In the last 3.5 ka, the lake has remained generally near or slightly above its present level. The depth and surface area of Lago Cardiel are controlled mainly by precipitation onto the lake and surrounding catchment, air and water temperature, and wind-speed related to local strength of the Southern Hemispheric Westerlies (SHW). Our lake-level reconstruction combined with evidence from other studies suggest that on average the core of the SHW was located well to the north (<45°S) of the Cardiel basin during the deep lake phase associated with the LGM, and was well to the south (>55°S?) during the hydrologic maximum of Cardiel in the early Holocene. The lower phases of the lake at 20.0–11.5, 8.5–7.5, and 5.0–3.3 ka generally correspond to cold conditions in other records, when we infer that the SHW were strongly focused around the latitudes of Cardiel at 49°S. Highlights: Our research tracks the changes in size of Lago Cardiel at southern South America over the past ∼40 thousand years. Lake expansions coincide with warm periods and lake contraction and even near drying with cold periods. A warming future world should eventually lead to an increase in the size of Lago Cardiel.